2018
DOI: 10.3389/fpls.2017.02260
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crops and Fertilization Alter Nitrogen Loss in Organic and Conventional Conservation Agriculture Systems

Abstract: Agroecosystem nitrogen (N) loss produces greenhouse gases, induces eutrophication, and is costly for farmers; therefore, conservation agricultural management practices aimed at reducing N loss are increasingly adopted. However, the ecosystem consequences of these practices have not been well-studied. We quantified N loss via leaching, NH3 volatilization, N2O emissions, and N retention in plant and soil pools of corn conservation agroecosystems in Kentucky, USA. Three systems were evaluated: (1) an unfertilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 64 publications
2
38
0
Order By: Relevance
“…Previous reviews have compared the net N 2 O emissions and NO 3 leaching from these systems. Lower areascaled, but roughly similar yield-scaled emissions (slightly higher, similar or slightly lower) are commonly observed for N 2 O emissions (Tuomisto et al, 2012;Skinner et al, 2014Skinner et al, , 2019 and NO 3 leaching (Kirchmann and Bergström, 2001;Stopes et al, 2002;Aronsson et al, 2007;Tuomisto et al, 2012;Benoit et al, 2014) from organic versus non-organic arable crop production.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…Previous reviews have compared the net N 2 O emissions and NO 3 leaching from these systems. Lower areascaled, but roughly similar yield-scaled emissions (slightly higher, similar or slightly lower) are commonly observed for N 2 O emissions (Tuomisto et al, 2012;Skinner et al, 2014Skinner et al, , 2019 and NO 3 leaching (Kirchmann and Bergström, 2001;Stopes et al, 2002;Aronsson et al, 2007;Tuomisto et al, 2012;Benoit et al, 2014) from organic versus non-organic arable crop production.…”
Section: Introductionsupporting
confidence: 58%
“…Weier et al, 1992;Li et al, 2005), we address how the supply of N and carbon (C) via organic inputs drive N 2 O emissions in organic arable rotations. Based on the IPCC (2006), most inventories and farm models assume that 1 % of total N-input by fertilisers, manure and plant residues are emitted as N 2 O-N. Skinner et al (2014) found no correlation between total N-input and N 2 O emission in organic systems. If this is a general trend, the total N-input cannot be used to estimate N 2 O emissions from organic crop rotations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An ignored yet important management factor that can influence cover crop tissue C and N estimation is sample‐grinding size. A broad range of sample‐grinding size, ranging anywhere from >2 mm to pulverized have been reported in the literature (Jahanzad et al, 2016; Etemadi et al, 2017; Shelton et al, 2018; Sievers and Cook, 2018), but no agreement about which sampling size is the most appropriate has been reached to present. In a literature review, we randomly assessed 36 peer‐reviewed journal articles, which reported cover crop C and N concentrations (Table 1; in addition, see online version of article for supplemental material).…”
Section: Frequency Of Sample‐grinding Size In 36 Randomly Published Pmentioning
confidence: 99%